Identifikasi Tutupan Tata Guna Lahan Menggunakan Citra Satelit Di Desa Tanjung Baru Kecamatan Baturaja Timur Kabupaten OKU - Azwar, Azwar; Lucyana, Lucyana; Meiwinda, Eka Rizki; Cahyo, Ali Mas’ud Dwi; Sapta, Andre Rayhan (UNIVED Press, 2026)
Land use changes occur from year to year. This information can be done periodically. There is a sensing technology used to describe objects and monitor changes in land use. The purpose of this study is to detect land use shifts in Tanjung Baru Village through satellite imagery. The data used is then analyzed through Land Use Analysis using ArcGIS Software with image maps from Google Earth. Tanjung Baru Village has an area of ​​442, 541 Ha. Tanjung Baru Village has areas such as residential areas with an area of ​​132, 532 ha, vacant land with an area of ​​75, 144 ha, plantations / forests with an area of ​​225, 050 ha and others with an area of ​​9,815 ha. The use of residential land is 30%, vacant land 17%, plantations / forests 51% and others 2%..